Diagnóstico poblacional de nemátodos fitoparásitos en el cultivo de sacha inchi (plukenetia volubilis l.) en la región San Martín - Shapiama Ramírez, Segundo Américo (2008)
The present investigation work one carries out collecting floor samples and roots he/she was carried out in four (4) sectors of the region San Martin: High May - Low May - Low Huallaga - Central Huallaga: each one of these sectors represented by sub productive sectors, of the cultivation of sacha inchi. The biological studies (floor analysis, roots) and physical (you show of floor), they were developed the Laboratory of the Institute of Tropical Cultivations (ICT). The identification of goods found in the floor and roots were carried out in the Laboratory of Fitopatología of the Institute of Tropical Cultivations (ICT). The investigation was basic by means of a design statistical non parameter or descriptive. To determine the external characteristics that it presents the nemátodos using key taxonómicas from Luc et to the one. (1990), Thorne (1961), Taylor (1968), Roman (1978) and Chestnut tree-Zapata and Salazar (1998). Presently work was the following thing: They have been nematodes of economic importance among the studied samples, for different cultivations, among endo parasite, semiendo parasite and ecto parasite, being that of more abundance and economic importance in the region the I generate Meloidogyne sp. Alone you reports in the roots of the cultivation of Sacha Inchi to the nematode of the I generate Meloidogyne sp being this the causing of the nodules and the damages in the plantations. The factor but influential in all the samples on the population of nematodes is the agricultural activity, that is to say Sacha inchi. The altitude is a decisive factor for the diversity nematodes in the region San Martin, but it doesn't stop the quantity of population, like it is shown in the evaluations. The humidity in the a floor sandy Franco has influence in the mobility of nematodes, making that these they reproduce but quickly because he stays near his guest, that is to say he has constant food.